Toward defining the Anthropocene onset using a rapid increase in anthropogenic fingerprints in global geological archives - Kuwae, Michinobu; Yokoyama, Yusuke; Tims, Stephen; Froehlich, Michaela; Fifield, L. Keith; Aze, Takahiro; Tsugeki, Narumi; Doi, Hideyuki; Saito, Yoshiki (Proceedings of the National Academy of Sciences - PNAS, 2024)
One of the remaining issues regarding the Anthropocene is the lack of stratigraphic evidence indicating when the cumulative human pressure from the early Holocene began to fundamentally change the Earth system. Herein, we compile anthropogenic fingerprints from various high-precision-dated proxy records for 137 global sites to determine the age of the unprecedented surge in these records over the last 7700 y. The cumulative number of fingerprints revealed an unprecedented surge in diverse anthropogenic fingerprints starting in 1952 ± 3 CE, corresponding to the onset of the Great Acceleration. Notably, the period from 1953 to 1958 CE saw a nearly simultaneous surge in fingerprints across all regions, including Antarctica, the Arctic, East Asia, Europe, North America, and Oceania. This synchronous upsurge reflects the moment when human impacts led to rapid transformations in various natural processes and cycles, with humans becoming a geological force capable of inscribing abundant and diverse anthropogenic fingerprints in global strata. Following this global fingerprint explosion, profound planetary-scale changes, including deviations from the established natural climatic conditions, begin. This unprecedented surge in anthropogenic signals worldwide suggests that human influences started to match many natural forces controlling the processes and cycles and overwhelm some of the functioning of the Earth system around 1952.